IMPLEMENTASI TEKNOLOGI WASTAFEL TANPA SENTUH DI RUMAH SAKIT KOTA PADANG DALAM RANGKA MEMUTUS MATA RANTAI COVID-19 - Zaini Zaini; Syarkawi Syamsuddin; Wisnu Joko Wulung; Purnawan Purnawan; Hendery Dahlan; Wisnel Wisnel; Denny Herald (LPPM Universitas Andalas, 2020)
The public's lack of concern for health protocols is directly proportional to the increase in the number of people affected by the Covid-19 virus. This condition worsens when public facilities such as available hand washing equipment tend to be less hygienic because there is still physical contact during the hand washing process, so there is a great potential risk of spreading the Covid-19 outbreak in the community en masse. Therefore an innovation was made in the form of a touchless hand washing device equipped with sensors to replace the function of water taps and manual liquid soap containers. The target audience of this activity is the people in the hospital environment of Padang City. This activity is carried out in two stages, namely the first stage to design tools and the second stage in the form of procurement of tools as well as outreach to the people of Padang City who visit the hospital regarding the introduction and how to use hand washing tools without touch as well as demonstrating to the community with the assistance of the hospital about how to wash hands properly and correctly according to health protocols.